Analisa Ketahanan Baterai Lithium Ion pada Sepeda Listrik Roda Tiga - Dewi, Dewi lestari; Susilo, Susilo; Widodo, Bambang (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2022)
Lithium-ion (Li-Ion) batteries are rechargeable batteries used to store and provide electrochemical energy. The purpose of this research is to find out the durability of lithium-ion batteries on three-wheeled electric bikes. Research methods used using quantitative descriptive methods. The durability of the lithium-ion battery on an electric bike during use (discharge) varies depending on the intensity of use. Loadless use tends to last longer, while heavy use reduces battery life. The first use of a lithium-ion battery with a voltage of 64.1 V, then after 5 minutes of use the battery decreased to 62.8 V and so on with a variable time efficiency. This factor needs to be taken into account to maintain the performance and battery life and the capacity of the lithium-ion battery on a three-wheel electric bike may change during the recharge cycle. Initially, after full charging, the battery capacity will be maximum. However, every time a battery is recharged and used, there are chemical changes in the battery cell that can result in a decrease in capacity over time and the number of recharging cycles.